Immunogenicity and protective efficacy of Clostridium difficile spore proteins. (February 2016) - Ghose, Chandrabali; Eugenis, Ioannis; Edwards, Adrianne N.; Sun, Xingmin; McBride, Shonna M.; Ho, David D.
Abstract: Clostridium difficile is a spore-forming, anaerobic, Gram-positive organism that is the leading cause of antibiotic-associated infectious diarrhea, commonly known as C. difficile infection (CDI). C. difficile spores play an important role in the pathogenesis of CDI. Spore proteins, especially those that are surface-bound may play an essential role in the germination, colonization and persistence of C. difficile in the human gut. In our current study, we report the identification of two surface-bound spore proteins, CdeC and CdeM that may be utilized as immunization candidates against C. difficile . These spore proteins are immunogenic in mice and are able to protect mice against challenge with C. difficile UK1, a clinically-relevant 027/B1/NAP1 strain. These spore proteins are also able to afford high levels of protection against challenge with C. difficile 630Δ erm in golden Syrian hamsters. This unprecedented study shows the vaccination potential of C. difficile spore exosporium proteins. Highlights: Clostridium difficile spore proteins play an important role in the disease pathogenesis of C. difficile infection (CDI). Exosporium spore proteins, that are present on the outermost surface of the spores, may be potential targets for vaccination. Exosporium proteins CdeC and CdeM are immunogenic and protective in animal models of CDI.